Why did Rwanda join British Commonwealth? : Explaining Rwanda’s Foreign Policy - Muhammad, Ali; Hutami, Amalia Nurul (Faculty of Economics and Social Science, Department of International Relations, Universitas Amikom Yogyakarta, 2021)
This article aims to examine Rwanda's foreign policy decision to join the British Commonwealth. Rwanda was former French colony and has historic association with Francophone countries. But the country decided to join the British Commonwealth in 2009. Using theory of foreign policy decision making, it argues that the shift of Rwanda’s foreign policy was caused by the political transition in Rwanda’s domestic politics, its economy condition in the post-genocide epoch as well as the international context which included Rwanda’s geographic position and the role of the United Kingdom in aiding Rwanda’s state-building in the aftermath of the genocide. This research uses qualitative method and uses secondary data such as, books, articles, journals, e-news, reports and other library sources.